The Influence of Electronic Word-of-Mouth on Social Media Towards Purchase Intention of Luxury Perfume Brands (Journal of Business and Management, 2022)
The number of middle and upper socioeconomic class in Indonesia continues to increase from year to year. Therefore, the luxury perfume brand industry makes Indonesia one of its priorities. As a result, Indonesia was recorded to contribute revenue to the sale of luxury goods as much as 2,035,000,000 USD in 2020, where luxury perfume brands have the highest sales figures. This high number cannot be separated from the influence of social media with the spread of information online or commonly called eWOM. Unfortunately, how eWOM on social media affects buying interest in luxury perfume brands is not fully understood. This study aims to find factors that influence consumers' purchase intentions for luxury perfume brands after seeing eWOM on social media and provide recommendations to luxury perfume brands in maximizing eWOM to be implemented in stimulating purchase intentions. The qualitative approach was conducted through interviews with 15 people and quantitative approach through a survey with a total of 300 respondents, where respondents had bought or used luxury perfume brands. The results of the interviews were analyzed using the open coding method and the survey results were analyzed using the PLS-SEM method. Based on the results of interviews, customer reviews on Instagram, TikTok, and YouTube are the most frequently used tools to find reviews about luxury perfume brands. The results of the survey show that perceived persuasion, source expertise, and source trustworthiness significantly influence consumers' purchase intentions towards luxury perfume brands after viewing eWOM on social media. The results of this study are expected to be useful for readers, eWOM senders, and luxury perfume brand industries in utilizing eWOM as a marketing strategy.Keywords: eWOM, luxury perfume brands, purchase intention, social media